In Psychology and Medicine Role of Gerontology - Abatbaeva Nargiza Jaksibaevna (Genius Publishing Group, 2021)
This article discusses the study of gerontology (old age) in medicine and psychology, changes in the human body and their impact on life, psychology and the human body.
Keywords: Gerontology; gerontopsychology; geriatrics; biological aging